Análise do comportamento da microestrutura de materiais endurecidos retificados com rebolos de CBN - Bianchi, Eduardo Carlos [UNESP]; Monici, Rodrigo Daun [UNESP]; Silva, Eraldo Jannone Da [UNESP]; Aguiar, Paulo Roberto De [UNESP]; Valarelli, Ivan De Domenico [UNESP] (ABM, ABC, ABPol, 2000)
CBN grinding wheels are superabrasive tools, with cutting ability higher than the conventional ones, specially used for grinding DTG (Difficult to Grind) materials. Due to the higher hardness and thermal conductivity of the CBN superabrasive grains, when compared with conventional abrasive grains, the use of CBN tools reduce the grinding temperatures decreasing the probability of workipece’s thermal damage. These proprieties of CBN grains permit lowering the energy partition because less heat is generated during grinding and much heat is dissipated through the grinding wheel instead of through the workpiece. This paper shows a research about the microstructural changes in the ground subsurface and the differences in the superficial integrity when using two types of superabrasive grinding wheels, manufactured with vitrified and resin bonds, analyzed in different cutting conditions. The ground material was the VC 131 steel, hardened and tempered. Were not observed microstructural changes in the subsurface ground with the two types of tools. As a result, the use of different types of the bonding do not affect the surface integrity neither resulted in microstructural changes, because the maximum temperatures measured in the grinding zone were lower than 125 °C, much less than the required level to cause microstructural changes.
Keywords: microstructure; CBN grinding wheel; resin bond; vitrified bond